Interface Design for the Mobile Terminal for Furniture Shopping in the Post-epidemic Era: An Empirical Evidence of User Demand Collection - Wangshu Zhang; Chengmin Zhou; Mengnan Yu; Ting Huang; Jake Kaner (BioResources, 2023)
The Internet economy is flourishing, and the form of consumption has shifted from offline brick-and-mortar shopping to online consumption. At the same time, COVID-19 led to many offline stores being constrained in many ways, accelerating the conversion of shopping. The purpose of the study is to enable users to effectively use mobile products and optimize their service experience during furniture consumption. This study compares the relevant theories and the current state of research. Through qualitative and quantitative methods, user needs are investigated and data analysis is conducted to summarize interface improvement suggestions. The high-fidelity prototype design was conducted, and the interactive prototype was delivered to users for testing to verify the effect and feasibility of interface optimization and to propose improvement suggestions for the mobile terminal of furnishings.